Integration of Photocatalysis and Membrane Technology as a Hybrid System for Microplastic Degradation in Wastewater - Sri Rahayu Dwi Purnaningtyas; Mila Sari; Eka Cahya Muliawati; Afridon (Science Journal Get Press, 2026)
Microplastic contamination in wastewater poses a serious threat to aquatic ecosystems and human health due to its persistence and limited removal by conventional treatment processes. This study evaluates a hybrid photocatalytic membrane reactor (PMR) integrating TiO₂-based photocatalysis with membrane filtration for the removal and degradation of polyethylene (PE), polypropylene (PP), and polyester (PET) microplastics. Photocatalytic membranes were fabricated via phase inversion using polyethersulfone (PES) and characterized by SEM, XRD, contact angle, porosity, and water flux measurements.TiO₂ incorporation significantly increased membrane hydrophilicity and permeability while maintaining the asymmetric structure and anatase crystallinity. The hybrid PMR achieved microplastic removal efficiencies above 99% for all polymers, outperforming membrane-only filtration and standalone photocatalysis. FTIR and SEM analyses confirmed oxidative polymer chain scission, while mineralization efficiencies reached 8.7%, 11.3%, and 18.9% for PE, PP, and PET, respectively. The degradation followed apparent first-order kinetics, with PET showing the highest rate constant. Hydroxyl radicals were identified as the dominant reactive species. The PMR also exhibited mitigated membrane fouling, stable performance over five cycles, and negligible TiO₂ leaching. The specific energy consumption ranged from 0.38 to 0.46 kWh m⁻³ with an estimated operational cost of USD 0.42–0.53 per m³. These findings demonstrate the technical and economic feasibility of the hybrid PMR for advanced microplastic treatment.